2016
DOI: 10.24846/v25i4y201601
|View full text |Cite
|
Sign up to set email alerts
|

Finite-Time Convergence Stability of Lur’e Discrete-Time Systems

Abstract: Abstract:In this paper, a constructive design methodology for Finite-Time Stability (FTS) of a class of nonlinear discrete-time systems is proposed. A dead-beat controller that can achieve n-finite-time stability is constructed. Furthermore, stability conditions, based on the use of Borne and Gentina practical stability criterion and matrices in the Benrejeb arrow form, are synthesized. Similarity between transient behaviors of dead-beat controlled linearized and nonlinear third order systems are shown and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Moreover, it was observed that under some matching conditions, the dead-beat controller based on the Tustin approximation leads to an n-finite-time stabilization of the exact sampled-data n order system. Developed results can be extended to finite-time stabilization of nonlinear systems as shown in [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it was observed that under some matching conditions, the dead-beat controller based on the Tustin approximation leads to an n-finite-time stabilization of the exact sampled-data n order system. Developed results can be extended to finite-time stabilization of nonlinear systems as shown in [23].…”
Section: Discussionmentioning
confidence: 99%
“…This note investigates the influence of the discretization method in the controlled system properties. The work is a continuation of the previous paper [23] in which the effects of a ZOH discretization on the stability and stabilization properties of linear and nonlinear Lure-type systems are considered. The aim of this paper is to investigate more discretization techniques, mainly, the forward Euler and the Tustin approximations, and study the impact of a numerical approximation on the control system (5) on the system properties in term of stability and finite-time stability.…”
Section: B Finite-time Stabilization and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation